Siswa Berduka di Indonesia Membutuhkan Pendidikan Kematian: Rekomendasi Penerapan Konseling di Sekolah - Novianti, Novianti; Supriatna, Mamat; Nadhirah, Nadia Aulia (Universitas Mathla'ul Anwar Banten, 2023)
The death of the closest people leaves a feeling of loss and grief that can last into adulthood if it is not resolved. Children and adolescents are the most vulnerable subjects due to a lack of understanding about death and grief. Unfortunately, death education in Indonesia is still minimal, even though it can help children cope with grief as a basic response to loss. Death education should be provided by guidance and counseling teachers, but no studies or practices in Indonesia apply to this context. Therefore, this research was conducted to make recommendations based on a literature review on death education to help students cope with grief. This study uses the systematic literature review (SLR) method which aims to synthesize and present in-depth data from 20 selected previous studies from Google Scholar, PubMed, Harzing, and Mendeley. The implementation of death education can be focused on the explanation of death, the value of life and death, and strategies to cope with the grief caused by death. Practical strategies to implement death education in Indonesia can be developed before being widely practiced.